Reducing oil absorption of falafel balls by using edible coating films containing dried orange-albedo powder or dried apple peel during deep frying - Angor, Malak (Frontiers in Sustainable Food Systems, 2023)
Introduction The purpose of this study is to examine the effects of varying proportions of dried-orange-albedo and dried-apple-peel powders in edible coating films for falafel balls on their subsequent oil uptake and sensory properties when used during deep frying in oil. Methods Coating solutions of 3%, 5%, and 7% w/v of either orange albedo or apple-peel powder were prepared and heated to 90°C for 5 min, after which they were cooled. In the next step, the falafel-ball samples were air-dried after dipping them in the coating solutions. The falafel balls coated with different solutions were then deep-fried and their oil and moisture content with the calculation of oil uptake and moisture retention was analyzed, along with the evaluation of sensory attributes. Results According to the results, oil uptake during deep oil frying was reduced to varying extents in all coating treatments. For both orange albedo and apple-peel powder, the coating films containing 5% of either were found to be the most effective level in reducing the oil uptakes. Discussions The coating films prepared from orange albedo reduced oil uptake more than those containing the same amount of apple peel for all levels. All falafel ball samples prepared with the different coatings were found to have improved sensory features compared with the uncoated control.